2010
DOI: 10.1016/j.micron.2010.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Probing magnetic order in EELS of chromite spinels using both multiple scattering (FEFF8.2) and DFT (WIEN2k)

Abstract: The electron energy loss near edge structure on the O K-edge from chromite spinels contains fine structure from the hybridisation of the O p-orbitals and the Cr d-orbitals. Unlike the aluminates, a non-spin polarised calculation of this fine structure differs significantly from experimental observations. This is due to the large magnetic moment on the Cr. Calculations using simplified collinear ordering of the spins and the local spin density approximation give much improved agreement. A real space multiple sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…We observed significant differences between ZnO and ZnCr 2 O 4 as shown in Figure 4c, indicative of the different bonding schemes in the two materials. For the O- K edge, there was only one peak observed in the ZnO matrix, in accordance with previous measurements [38,39,40], while an obvious splitting occurred in ZnCr 2 O 4 , agreeing well with earlier reports [41,42,43], as also illustrated in Figure 4d. This was because in the ZnO unit cell, there was only one tetrahedron, which was composed of Zn and its four surrounding O, and each Zn-O bond exhibited a length of 1.98 Å.…”
Section: Resultssupporting
confidence: 93%
“…We observed significant differences between ZnO and ZnCr 2 O 4 as shown in Figure 4c, indicative of the different bonding schemes in the two materials. For the O- K edge, there was only one peak observed in the ZnO matrix, in accordance with previous measurements [38,39,40], while an obvious splitting occurred in ZnCr 2 O 4 , agreeing well with earlier reports [41,42,43], as also illustrated in Figure 4d. This was because in the ZnO unit cell, there was only one tetrahedron, which was composed of Zn and its four surrounding O, and each Zn-O bond exhibited a length of 1.98 Å.…”
Section: Resultssupporting
confidence: 93%
“…This increase in oxidation state is often associated with cation sites that deviate from the centrosymmetric, and transitions at energies below the absorption edge (“pre-edge transitions”) intensify. These phenomena have been reported for almost all transition metals [96,97,98]. …”
Section: X-ray Absorption Fine Structure Spectroscopymentioning
confidence: 53%
“…32 The O K edge may therefore be sensitive to the TM 3d states, and correct handling of any magnetic interactions may become particularly important. For example, Eustace and co-workers 4 found that a correct description of magnetic interactions was essential to model the O K edges of a series of chromite spinels. We should therefore investigate whether these interactions are of similar importance in the case of AlV 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…To this end, experimental studies of the electronic structure using photoemission spectroscopy or electron energy-loss spectroscopy can provide invaluable contributions, [1][2][3] in particular when combined with electronic structure calculations from first principles. 4,5 At high temperature, AlV 2 O 4 is a cubic spinel with Al on the tetrahedral sites and V on the octahedral sites. At approximately 700 K, there is a structural phase transition to a lower-symmetry trigonal structure.…”
Section: Introductionmentioning
confidence: 99%